Radiolabeling of Herceptin with 99mTc as a Her2 tracer - Heydari, Samira; Rajabi, Hossein; Rasaneh, Samira; Johari Daha, Fariba (Novelty in Biomedicine, 2014)
Introduction: Trastuzumab is a monoclonal antibody that is used in treating breast cancer. We labeled this monoclonal antibody with Technetium-99m and performed in vitro and in vivo quality control tests as a first step in the production of a new radiopharmaceutical. Methods: Trastuzumab was labeled with Technetium-99m using Succinimidyl Hydrazinonicotinamide (HYNIC) as chelator. Radiochemical Purity and stability in buffer and serum were determined. Immunoreactivity and toxicity of the complex were tested on SKBR3, MCF7 and A431 breast cancer cell lines. Biodistribution study was performed in normal mice at 4 and 24 h post injection. Results: The radiochemical purity of the complex was 95±1.4%. The stabilities in phosphate buffer and in human blood serum at 24 h post preparation were 85±3.5% and 74±1.2%, respectively. The immunoreactivity of the complex was 86±1.4%. The binding of labeled antibody to the surface of SKBR3, MCF7 and A431 cells were increased by increasing Her2 concentration on the cells surface. Conclusions: The findings showed that the new radiopharmaceutical can be a promising candidate as Her2 antigen scanning for human breast cancer.